2019
DOI: 10.1111/hepr.13346
|View full text |Cite
|
Sign up to set email alerts
|

Branched chain amino acids are associated with the heterogeneity of the area of lipid droplets in hepatocytes of patients with non‐alcoholic fatty liver disease

Abstract: Aim Macrovesicular steatosis around the central vein (zone 3) is one of the pathological features of non‐alcoholic fatty liver disease or steatohepatitis (NAFLD/NASH). The aim of this study is to elucidate precisely the association between the area of lipid droplets (LDs) and the plasma metabolic parameters in patients with NAFLD/NASH. Methods Eighty patients with NAFLD/NASH diagnosed by needle biopsy were enrolled. The LDs around zone 3 were counted automatically by image processing software, the total area o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
17
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 40 publications
(69 reference statements)
0
17
1
Order By: Relevance
“…In particular, branched-chain amino acids (BCAAs, leucine, isoleucine, and valine) have been proved to be elevated in NAFLD patients [9], and strongly associated with increased risk of NAFLD [10], insulin resistance, obesity [11,12] and future clinical decompensation in NAFLD [13]. It was also revealed that the changes in hepatic BCAA composition were strongly associated with transcriptomic metabolism pro les during the progression of NAFLD [14]. Various exercise intensities impacted plasma metabolic pro le differently [15][16][17], for now, there were fewer studies that examined the circulating AAs alteration after exercise training [18][19][20][21][22], and the relationship between AAs metabolism and exercise intensity was little known.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, branched-chain amino acids (BCAAs, leucine, isoleucine, and valine) have been proved to be elevated in NAFLD patients [9], and strongly associated with increased risk of NAFLD [10], insulin resistance, obesity [11,12] and future clinical decompensation in NAFLD [13]. It was also revealed that the changes in hepatic BCAA composition were strongly associated with transcriptomic metabolism pro les during the progression of NAFLD [14]. Various exercise intensities impacted plasma metabolic pro le differently [15][16][17], for now, there were fewer studies that examined the circulating AAs alteration after exercise training [18][19][20][21][22], and the relationship between AAs metabolism and exercise intensity was little known.…”
Section: Introductionmentioning
confidence: 99%
“…Besides the known mechanisms for zone 3 steatosis, a recent study by Kakazu et al . was the first to show that BCAAs are an independent factor associated with the steatosis in zone 3 hepatocytes in patients with NAFLD/NASH . Although higher serum level of BCAAs have been reported in a mouse model of NASH as well as in patients with NAFLD/NASH, Kakazu et al .…”
mentioning
confidence: 98%
“…The recent article by Kakazu et al . showed that branched‐chain amino acids (BCAAs) are associated with the heterogeneity of hepatic steatosis in patients with NAFLD/NASH . Their findings indicated that an alteration in BCAA metabolism might be a pathological condition of NAFLD/NASH.…”
mentioning
confidence: 99%
See 2 more Smart Citations